ANALISIS YURIDIS NORMATIF UNDANG-UNDANG PEMILIHAN KEPALA DAERAH TENTANG PENCALONAN MANTAN PELAKU TINDAK PIDANA KORUPSI - Yuli Kasmarani (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research is motivated by a phenomenon that tends to consider corruption as a common practice. Therefore, researchers are interested in examining in depth the government's efforts to prevent the recurrence of perpetrators of corruption to become regional heads, and how is the normative juridical analysis of the Regional Head Election Law regarding the nomination of former perpetrators of corruption? This research is a normative juridical research, with a qualitative approach, namely the researcher starts from the data, then uses the existing theory as an analytical tool. Sources of data used in this study is secondary data. Secondary data is data obtained from official documents, books related to the object of research, after the data or legal materials needed in this research are collected, the legal materials are analyzed descriptively-analytical, namely explaining or describing all the research results on the main points of the problem, then the explanations are concluded and presented in the form of deductive paragraphs. The results of this study are that corruption is an extraordinary crime, therefore the government through Article 7 letter g of Law Number 8 of 2015 concerning Regional Head Elections has attempted to prevent former perpetrators of corruption by providing additional punishment. in the form of revocation of the right to vote and be elected (political rights) in order to provide a deterrent effect for perpetrators, prevent other officials from being corrupted and so that the human rights of others are implemented. Then, the condition that the candidate for regional head is not currently convicts of any crime, except for former convicts who are willing to publicly announce their identity if they are ex-convicts, this requirement is not in line with the provisions of Islamic law which prioritizes benefit and eliminates harm. So to be a leader, both central and regional leaders in Islam, one must have good scientific, religious and moral integrity Keywoard: Regional Head Election, Corruption Crime